Islamic character education model: An in-depth analysis for Islamic boarding school - Miftahuddin, Miftahuddin; Aman, Aman; Yuliantri, Rhoma Dwi Aria (LPMPP Universitas Negeri Yogyakarta, 2024)
This study aims to examine the implementation model of instilling Islamic characters at SMP-SMA Al-Irsyad Al-Islamiyyah Boarding School Purwokerto. This study employs a qualitative research design, utilizing observation, interviews, and document analysis as data collection techniques. The collected data are then analyzed to understand the character education model at Al-Irsyad. The research findings indicate that the formation of Islamic characters at SMP-SMA Al-Irsyad Al-Islamiyyah Boarding School Purwokerto is conducted through Islamic Religious Education (PAI) subjects, which include Akhlaq (ethics), Aqidah (creed), Fiqh (Islamic jurisprudence), and Tarikh Islam (Islamic history) as the learning materials. The Akhlaq lesson aims to promote honesty, integrity, and noble character for the students while eliminating feelings of envy. Meanwhile, the specific goal of Islamic character formation is instilled through Aqidah lesson. The Aqidah curriculum directs students to avoid practices in Islam that are considered deviant from monotheism, such as acts of shirk (polytheism), Tawassul (seeking intercession), and Tabarruk (seeking blessings). Some implications of this understanding result in Al-Irsyad not allowing the students to